Esaias Boursse’s ‘Tijkenboeck’: A Pictorial Catalogue of People Working and Living in and around Colombo, 1662 - Wagenaar, Lodewijk; Beumer, Mieke (The Rijksmuseum Bulletin, 2019)
We do not know who trained Esaias Boursse (1631-1672) to be a painter, but we do know that he became a member of the Amsterdam Guild of St Luke around 1651. He certainly did not have a successful career because he joined the Dutch East India Company (VOC) in 1661. He travelled to Colombo, the capital of the island of Ceylon (Sri Lanka since 1972), captured six years earlier by the Portuguese, by way of Batavia (now Jakarta). In 1663 he was back in Amsterdam – remarkable, as the standard contract with the VOC was for five years. In financial straits again, he re-joined the VOC in 1671 and left for Asia. Shortly after leaving he died at sea. In 1996 an album containing 116 drawings came to light, most of them made by Boursse during his time in Ceylon; he made only a small number during his outward or return journeys to the Cape of Good Hope. The drawings are completely different from his earlier known oeuvre of genre paintings and prints with religious themes. The pages in his ‘Tijkenboeck’ provide a unique picture of what Boursse saw in and around Colombo. They are important evidence of the early days of the VOC in its conquered colony of Ceylon.